Stephanie Guyer-Stevens and Françoise Pommaret, Divine Messengers: The untold story of Bhutan’s female shamans - Sumegi, Angela (Matrix, 2026)
Angela Sumegi reviews the monograph from Stephanie Guyer-Stevens and Françoise Pommaret monograph entitled Divine Messengers: The untold story of Bhutan’s female shamans.